2019
DOI: 10.3390/biom9100560
|View full text |Cite
|
Sign up to set email alerts
|

Linking Dysregulated AMPK Signaling and ER Stress in Ethanol-Induced Liver Injury in Hepatic Alcohol Dehydrogenase Deficient Deer Mice

Abstract: Ethanol (EtOH) metabolism itself can be a predisposing factor for initiation of alcoholic liver disease (ALD). Therefore, a dose dependent study to evaluate liver injury was conducted in hepatic alcohol dehydrogenase (ADH) deficient (ADH−) and ADH normal (ADH+) deer mice fed 1%, 2% or 3.5% EtOH in the liquid diet daily for 2 months. Blood alcohol concentration (BAC), liver injury marker (alanine amino transferase (ALT)), hepatic lipids and cytochrome P450 2E1 (CYP2E1) activity were measured. Liver histology, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Experimental evidence suggests that dysregulation of unfolded protein response (UPR) induced by endoplasmic reticulum (ER) stress in acinar cells after chronic alcohol consumption promotes the development of pancreatitis (Lugea et al, 2017a; Pandol et al, 2010). On the other hand, dysregulation of AMP‐activated protein kinase (AMPKα), a major regulator of cellular metabolism and ER/oxidative stress (Kim et al, 2015; Steinberg & Kemp, 2009), plays a key role in the pathogenesis of various diseases, including EtOH‐related disorders (Chen et al, 2010; Kaphalia et al, 2019; Liangpunsakul et al, 2010; Shearn et al, 2014; Srinivasan et al, 2019). An underlying link between EtOH‐induced AMPKα inactivation and ER/oxidative stress in relation to pancreatic acinar cell injury, and its inflammatory responses and cellular bioenergetics could be key factors for the initiation of ACP (Srinivasan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental evidence suggests that dysregulation of unfolded protein response (UPR) induced by endoplasmic reticulum (ER) stress in acinar cells after chronic alcohol consumption promotes the development of pancreatitis (Lugea et al, 2017a; Pandol et al, 2010). On the other hand, dysregulation of AMP‐activated protein kinase (AMPKα), a major regulator of cellular metabolism and ER/oxidative stress (Kim et al, 2015; Steinberg & Kemp, 2009), plays a key role in the pathogenesis of various diseases, including EtOH‐related disorders (Chen et al, 2010; Kaphalia et al, 2019; Liangpunsakul et al, 2010; Shearn et al, 2014; Srinivasan et al, 2019). An underlying link between EtOH‐induced AMPKα inactivation and ER/oxidative stress in relation to pancreatic acinar cell injury, and its inflammatory responses and cellular bioenergetics could be key factors for the initiation of ACP (Srinivasan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Of note, a majority of the ingested EtOH is metabolized primarily by oxidative metabolism to acetaldehyde by hepatic alcohol dehydrogenase (ADH), which is reduced during chronic alcohol consumption (Kaphalia et al, 1996; Nuutinen et al, 1983; Panes et al, 1993; Sharkawi, 1984). Furthermore, the hepatic ADH deficiency in deer mice fed chronic EtOH is shown to elevate body burden of EtOH despite the induction of hepatic cytochrome P450 2E1 (CYP2E1) (Srinivasan et al, 2019) and facilitates formation of FAEEs by several folds in the pancreas causing pancreatic injury (Amer et al, 2018; Bhopale et al, 2006; Kaphalia et al, 2010). During chronic EtOH ingestion, EtOH is predominantly metabolized via nonoxidative metabolism in the pancreas, catalyzed by FAEE synthase (Kaphalia & Ansari, 2003; Laposata & Lange, 1986; Werner et al, 1997; Werner et al, 2001; Werner et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis of alcohol fatty liver is complex, but the essence is mainly through the influence of alcohol dehydrogenase (ADH) (70–80%) and cytochrome P4502E1 (CYP2E1) enzyme activity [ 78 ] of microsomal ethanol oxidation system (MEOS) (10–25%), influence of ethanol metabolism; ADH enzyme activity [ 79 ] regulates lipid metabolism by affecting SIRT1 [ 80 ], AMPK [ 79 ], SREBP-1C, ChREBP, and PPAR- α . Moreover, CYP2E1 can induce oxidative stress, autophagy, and apoptosis via producing a series of ROS and endotoxin after alcohol [ 4 ]; the study shows PCP in the treatment of alcohol fatty liver from the essence of the ADH, CYP2E1 enzyme activity, and then it regulates ethanol metabolism, which is unified with the theory of Chinese medicine “both the symptoms and the treatment.”…”
Section: Discussionmentioning
confidence: 99%
“…AMPK [ 88 ] is an intracellular energy sensor and activation of this enzyme inhibits anabolic pathways while promoting lipid decomposition of metabolic processes [ 89 ], ADH and/or acute ethanol-induced cardiac contraction, and intracellular Ca 2+ responses with hyperactivation AMPK signaling cascade [ 90 ], phosphorylating downstream targets, including ACC which ultimately promotes long-chain fatty acids of β oxidation and leads to decreased accumulation of lipids in tissues, and the increased lipofuscin signaling allows the liver to stimulate AMPK [ 79 ] in the liver by lipofuscin resulting in the development of new lipid metabolism [ 91 ]. Hepatic fatty acid oxidation is increased [ 92 ], thereby preventing hepatic lipid accumulation in ethanol-fed mice after resveratrol, instead of PCP [ 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ethanol consumption is also known to decrease both sirtuin 1 (SIRT1) activity and expression, promoting lipogenesis with inflammation [ 119 , 120 , 121 ]. Studies based on the improvement of the adenosine monophosphate-activated protein kinase (AMPK)/(SIRT1) pathway in vivo and in vitro concerning alcohol induced hepatotoxicity, revealed the upregulation of SOD and GSH activity and decreased MDA activity [ 122 , 123 , 124 , 125 ]. Lee et al in their recent survey confirmed a crucial role of the SIRT1 pathway in alcohol exposure.…”
Section: Antioxidants Ald Exacerbation and Signaling Pathwaysmentioning
confidence: 99%